2015
DOI: 10.18632/oncotarget.3802
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-451 regulates stemness of side population cells via PI3K/Akt/mTOR signaling pathway in multiple myeloma

Abstract: Side population (SP) cells are an enriched source of cancer-initiating cells with stemness characteristics, generated by increased ABC transporter activity, which has served as a unique hallmark for multiple myeloma (MM) stem cell studies. Here we isolated and identified MM SP cells via Hoechst 33342 staining. Furthermore, we demonstrate that SP cells possess abnormal cell cycle, clonogenicity, and high drug efflux characteristics-all of which are features commonly seen in stem cells. Interestingly, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 33 publications
2
84
0
Order By: Relevance
“…These results suggest that miR451a plays an important regulatory role in pathogenesis and drug-resistance in the progression of CML. Other studies demonstrated that the down-regulated expression of miR-451a was closely related to the pathogenesis of various hematological malignancies involved in multiple myeloma [33,34], acute myeloid leukemia [35,36], acute lymphoblastic leukemia [37,38], myelodysplastic syndrome [39] and polycythemia vera [40]. In addition, miR-451a was required for erythroid homeostasis [41].…”
Section: Oncotarget S474 Wwwimpactjournalscom/oncotargetmentioning
confidence: 99%
“…These results suggest that miR451a plays an important regulatory role in pathogenesis and drug-resistance in the progression of CML. Other studies demonstrated that the down-regulated expression of miR-451a was closely related to the pathogenesis of various hematological malignancies involved in multiple myeloma [33,34], acute myeloid leukemia [35,36], acute lymphoblastic leukemia [37,38], myelodysplastic syndrome [39] and polycythemia vera [40]. In addition, miR-451a was required for erythroid homeostasis [41].…”
Section: Oncotarget S474 Wwwimpactjournalscom/oncotargetmentioning
confidence: 99%
“…As a novel anti-myeloma agent, suppressor of miR-451 increased the effectiveness of myeloma treatment by reducing MDR1 mRNA expression, decreasing clonogenicity, and inducing apoptosis [19]. In this study, we found that the apoptotic proportion of CSCs was evidently decreased in cells transfected with miR-19b.…”
Section: Discussionmentioning
confidence: 52%
“…Differential expression of TSC1 is also involved in the onset of MM and is associated with significant upregulation of miR-19b [18][19][20]. In this study, we performed in silico analysis and found miR-19b practically targeted TSC1.…”
Section: Introductionmentioning
confidence: 85%
“…PI3K/Akt/mTOR pathway is activated and play a critical role in MMSCs. Du et al [90] found that PI3K/Akt/mTOR signal transduction proteins CAB39, TSC1, P - S6 and P - P70S6K expression levels were significantly higher in SP cells of MM than that in MP cells of MM. Moreover, the mTOR specific inhibitor rapamycin can dramatically decrease the proportion of SP cells of MM.…”
Section: Signaling Pathwaysmentioning
confidence: 99%